Prakash J

80 Reputation

3 Badges

2 years, 124 days

MaplePrimes Activity


These are questions asked by Prakash J

eq1:=( d)/(dt)u+(d^(2))/(dy^(2))u + s*( d)/(dy)u + delta * theta = 0;

eq2:=( d)/(dt)theta + (d^(2))/(dy^(2))theta + s*Pr*( d)/(dy)theta +lambda* exp(theta/(1 +(epsilon*theta))) = 0; 

initial and boundary conditons   

t <=0; u = theta = 0, for 0 <= y  <= 1   

t> 0;  u =0, theta = 0   at  y = 0;  

t> 0;  u =1, theta = 0   at   y = 1  ;

where, s, epsilon, Pr, lambda, delta are arbitrary parameters

eq1 := diff(f(x), x, x, x)+(1/2)*cos(alpha)*x*(diff(f(x), x, x))+(1/2)*sin(alpha)*f(x)*(diff(f(x), x, x)) = 0;

eq2 := diff(g(x), x, x)+diff(g(x), x)+(diff(g(x), x))*(diff(h(x), x))+cos(alpha)*x*(diff(g(x), x))+sin(alpha)*f(x)*g(x) = 0;

eq3 := diff(g(x), x, x)+diff(h(x), x, x)+1/2*(cos(alpha)*x+sin(alpha)*f(x)) = 0

ics := f(0) = 0, (D(f))(0) = 1, ((D@@2)(f))(0) = a[1], g(0) = 1, (D(g))(0) = a[2], h(0) = 1, (D(h))(0) = a[3];

 

where p, q, r, a are positive constants and phi(0) be a initial condition

eq1 := diff(x(t), t) = x(K[1]-x(t))-p*x(t-tau[1])*y(t); eq2 := diff(y(t), t) = y(K[2]-x(t))-q*y(t-tau[2])*x(t);
(x*, y*):= (p*K[2]-k[1])/(p*q-1), (q*K[1]-k[2])/(p*q-1);

where, k_1, k_2, p, q, tau_1, tau_2 are positive constants

How to plot this equation with explore or animation

E[1]:=Sum((GAMMA(((beta+1)n-gamma(nu-1))+k))/(GAMMA(((beta+1)n-gamma(nu-1)))*GAMMA(rho*k + (nu(1-mu)+mu(2 n+1))))*((omega*t^(p))^(k))/(k!),k=0..5);  E[2] :=Sum((GAMMA((gamma(n+1)-beta *n)+k))/(GAMMA((gamma(n+1)-beta *n))*GAMMA(rho*k + (mu(2 n+1))))*((omega*t^(p))^(k))/(k!),k=0..5);    y(p):=Sum(c*gamma^(n)*t^(nu*(1-mu)+mu+2*mu*n-1)*E[1]+gamma^(n)t^(mu(2 n+1)-1)*E[2]*g, n=0..5);

with the conditions

mu, nu \in (0, 1); omega \in R; rho > 0; gamma, beta > or = 0; c & g are constant

1 2 3 4 Page 1 of 4